The female memory factory: How the gendered labour of memory creates mnemonic capital. Issue 3 (August 2019) - Reading, Anna
Within feminist memory studies the economy has largely been overlooked, despite the fact that the economic analysis of culture and society has long featured in research on women and gender. This article addresses that gap, arguing that the global economy matters in understanding the gender of memory and memories of gender. It models the conceptual basis for the consideration of a feminist economic analysis of memory that can reveal the dimensions of mnemonic transformation, accumulation and exchange through gendered mnemonic labour, gendered mnemonic value and gendered mnemonic capital. The article then applies the concepts of mnemonic labour and mnemonic capital in more detail through a case study of memory activism examining the work of the Parragirls and the Parramatta Female Factory Precinct Memory Project (PFFP) in Sydney, Australia. The campaigns have worked to recognize the memory and history of the longest continuous site of female containment in Australia built to support the British invasion. The site in Parramatta, which dates from the 1820s, was a female factory for transported convicts, a female prison, an asylum for women and girls, an orphanage and then Parramatta Girls Home. The Burramattagal People of Darug Clan are the Traditional Owners of the land and the site is of practical and spiritual importance to indigenous women. This local struggle is representative of a global economic system of gendered institutionalized violence and forgetting, The analysis shows how the mnemonic labour of women survivors accumulates as mnemonic value that is then transformed into institutional mnemonic capital. Focusing on how mnemonic labour creates lasting mnemonic capital reveals the gendered dimensions of memory which are critical for ongoing memory work.